2002
DOI: 10.1021/ja025788v
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Biotin Chain-Terminated Glycopolymers for Surface Glycoengineering

Abstract: Biotin chain-terminated glycopolymers were generated by cyanoxyl-mediated free-radical polymerization using a biotin-derivatized arylamine initiator with high conversion (75%) and low polydispersity (1.30). Streptavidin-biotinylated glycopolymer binding was verified by SDS-PAGE gel shift assay and patterned glycocalyx-mimetic surfaces successfully fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 12 publications
(15 reference statements)
1
105
0
Order By: Relevance
“…46,[66][67][68][69][70] In the present work we aimed to modify our "click" approach to glycopolymers for the synthesis of R-mannopyranosidecontaining glycoprotein mimics suitable for probing interactions with mannose-binding lectin (MBL), a key mammalian lectin of the immune system. Mannoside structures are prevalent on the cell surfaces of many bacterial and fungal pathogens, their arrangements distinct from human mannoside glycans, thus being distinguishable from the human host.…”
Section: Introductionmentioning
confidence: 99%
“…46,[66][67][68][69][70] In the present work we aimed to modify our "click" approach to glycopolymers for the synthesis of R-mannopyranosidecontaining glycoprotein mimics suitable for probing interactions with mannose-binding lectin (MBL), a key mammalian lectin of the immune system. Mannoside structures are prevalent on the cell surfaces of many bacterial and fungal pathogens, their arrangements distinct from human mannoside glycans, thus being distinguishable from the human host.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since streptavidin is a tetramer with four binding sites, each site binding to one molecule of biotin, it has been shown that surface engineering of various other biotinylated proteins on streptavidin-bound surfaces is possible. 44,47,[49][50][51] An alkoxyamine initiator bearing biotin was synthesized for the preparation of patterned brush layers end-capped with biotin functionality for the selective attachment of streptavidin protein. Hydroxymethyl-functionalized alkoxyamine, 3, was chosen as the precursor for the functionalization scheme ( Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Chaikof et al have explored the applicability of cyanoxyl-mediated radical polymerization (CMRP) in the synthesis of well-defined glycopolymers directly from unprotected glycomonomers [76][77][78][79][80][82][83][84][85]102,103]. As first noticed by Druliner in the early 1990s and by Gnanou more recently [69][70][71], a certain degree of control can be achieved when (meth)acrylic monomers are polymerized in the presence of cyanoxyl persistent radicals.…”
Section: Alkene Monomersmentioning
confidence: 99%
“…The resulting polymers were used to fabricate a series of glycocalyx-mimetic surfaces that showed uniform carbohydrate coating on a membrane-like thin film [84,85] and to functionalize quantum dots and magnetic beads [82].…”
Section: (Meth)acrylamide Monomersmentioning
confidence: 99%